The Link Between ESG Reporting Quality and Accounting Measures of Firm-Level Performance - Badingatus Solikhah; Pei-Yu Weng (Jurnal Dinamika Akuntansi, 2024)
Purpose: Sustainability reports and integrated information e.g. ESG reports, are utilized by stakeholders for various decision-making processes. Using Taiwan setting, this study examines the effect of ESG reporting quality, including ESG Score, ESG Rating, and ESG Ranking, on financial performance. Method: We employ 6,386 firm-year observations from Taiwanese non-financial listed companies to test the hypotheses. We investigate the relationship between ESG reporting quality and the financial performance of operating and market indicators at the firm level. We analyze ESG reporting components using the same pattern and perform two kinds of robustness checks, include Covid-19 period check and industry effect testing. Result: Empirical evidence demonstrates a positive effect on ESG reporting toward Tobin's Q and is robust in some testing, suggesting that ESG information has valuation implications.  In addition, ESG Rating provides the greatest contribution to operating performance and market performance as measured using Tobin's Q. Novelty: This study provides current empirical evidence on the relationship between ESG reporting quality and firm-level financial performance, going beyond conventional metrics such as Tobin's Q to incorporate a wider range of variables. This work explores various measures of ESG reporting, including ESG Score, ESG Rating, and ESG Ranking. Beyond a single metric, this comprehensive analysis of ESG reporting has numerous implications for firm performance.